Understanding the electronical and optical properties of 2D TMDs in electrochemical cells for advanced solar energy and photocatalytic applications - Almaraz, Rafael, author; Sambur, Justin, advisor; Ackerson, Chris, committee member; Bailey, Travis, committee member; Neilson, Jamie, committee member (Colorado State University. Libraries, 2025)
This dissertation explores the potential of two-dimensional (2D) transition metal dichalcogenides (TMDs) for advanced solar energy conversion, focusing on the unique behavior of monolayer (ML) molybdenum disulfide (MoS2) in electrochemical environments. The research is motivated by the urgent need for cleaner energy sources, particularly solar energy, which has the potential to significantly reduce global dependence on fossil fuels. In Chapter 1, the introduction highlights the limitations of conventional semiconductors in solar energy conversion, such as thermalization losses, and emphasizes the need for efficient energy storage and conversion systems. The unique properties of 2D semiconductors, such as the potential for hot carrier extraction and tunable band gaps, are introduced as promising solutions to overcome these challenges. In Chapter 2, the theoretical framework for semiconductor photoelectrochemistry is discussed, with an emphasis on the challenges associated with interfacial electron transfer at semiconductor-liquid interfaces. Traditional semiconductor behavior, including band edge stability and electron transfer kinetics, is contrasted with the dynamic behavior observed in 2D materials. This chapter also introduces methods such as Mott-Schottky analysis and in situ spectroelectrochemical techniques to quantify band edge movement and energy levels in 2D semiconductors. Chapter 3 investigates the phenomenon of band gap renormalization (BGR), where the electronic bandgap of 2D materials shifts dramatically due to changes in carrier concentration. Using in situ spectroelectrochemical measurements, the research quantifies the BGR effect in ML-MoS2, showing significant band gap shifts of over 200 meV in response to changes in applied potential and redox conditions. The impact of these shifts on electron transfer kinetics is analyzed, revealing the potential to tune energy levels and enhance solar energy conversion efficiency. In Chapter 4, the research delves deeper into the BGR effect, demonstrating that charge equilibration at the semiconductor-redox electrolyte interface drives substantial band edge movement. By examining ML-MoS2 in various redox environments, the study reveals how redox potentials influence band gap renormalization, providing insights into the energetics of 2D semiconductor-electrolyte interfaces. This chapter highlights the fundamental differences between bulk and 2D semiconductors, opening new avenues for manipulating electron transfer kinetics in energy applications. Chapter 5 discusses ongoing efforts to harness high-energy quantum states in 2D materials for bio-inspired photocatalysis and solar fuel generation. The chapter emphasizes the potential of 2D semiconductors to capture and utilize high-energy carriers from the solar spectrum, offering a pathway to more efficient and sustainable energy conversion processes. Finally, Chapter 6 concludes the thesis with suggestions for subsequent investigations available based on the expertise and resources within the Sambur group at Colorado State University.